Countering depopulation in Kansas: understanding perceptions of rural life and the effectiveness of the Rural Opportunity Zone Program - Brooks, Matthew M. (Kansas State University, 2017)
Many rural areas throughout the Great Plains and Midwest have been affected by a “brain drain,” or the outward migration of highly trained or well-educated people. This hurts many facets of rural communities, including local schools, economies, and available services. In response to a negative outlook for rural areas, in 2012 the State of Kansas implemented the Rural Opportunity Zone (ROZ) Program to encourage young, college-educated adults to move to rural counties. The ROZ program provides tax waivers and student loan repayments to those willing to relocate to participating counties. This research looks at what influences young educated adults to participate in the program as well as how the ROZ’s financial benefits potentially outweigh the drawbacks associated with rural life. The research employed a survey of Kansas State University students as well as interviews with local economic development officials who manage the program. Survey results reveal that even though the majority of students have a stated rural preference most do not view themselves as likely to participate in the program. Despite student interest in the program benefits most view the lack of services and employment opportunities in rural Kansas to be too much of a drawback. County officials expressed similar feelings. Interviews revealed that, though the program primarily benefits those though were already intending to live in a rural area, the program rarely attracts newcomers. In addition, the program is poorly funded in many areas and the lack of affordable housing or high paying jobs limits population growth in a way that the benefits of the ROZ cannot outweigh. Findings from this research will allow communities to make changes that build upon their attributes as well as limit their undesirable characteristics. This research also highlights the need for changes to be made by the State of Kansas concerning the program’s benefits and awareness.
Keywords: Population; Migration; Rural; Community; Opportunity Zone Program; Policy